A Novel Rab9 Effector Required for Endosome-to-TGN Transport - Díaz, Elva (The Rockefeller University Press, 1997)
Rab9 GTPase is required for the transport of mannose 6-phosphate receptors from endosomes to the trans-Golgi network in living cells, and in an in vitro system that reconstitutes this process. We have used the yeast two-hybrid system to identify proteins that interact preferentially with the active form of Rab9. We report here the discovery of a 40-kD protein (p40) that binds Rab9–GTP with roughly fourfold preference to Rab9–GDP. p40 does not interact with Rab7 or K-Ras; it also fails to bind Rab9 when it is bound to GDI. The protein is found in cytosol, yet a significant fraction (∼30%) is associated with cellular membranes. Upon sucrose density gradient flotation, membrane- associated p40 cofractionates with endosomes containing mannose 6-phosphate receptors and the Rab9 GTPase. p40 is a very potent transport factor in that the pure, recombinant protein can stimulate, significantly, an in vitro transport assay that measures transport of mannose 6-phosphate receptors from endosomes to the trans-Golgi network. The functional importance of p40 is confirmed by the finding that anti-p40 antibodies inhibit in vitro transport. Finally, p40 shows synergy with Rab9 in terms of its ability to stimulate mannose 6-phosphate receptor transport. These data are consistent with a model in which p40 and Rab9 act together to drive the process of transport vesicle docking.